1980
DOI: 10.1177/001872088002200406
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Performance During Acute Alcohol Intoxication and Hangover

Abstract: Eleven private pilots (seven men and four women) were recruited and trained on the Multiple Task Performance Battery (MTPB), static and dynamic tracking of a localizer/glide slope instrument, and use of the Intoxilyzer. The experiment comprised four test sessions (vodka, bourbon, placebo, and control sessions) held at weekly intervals. Sessions began at about 5:00 p.m. and continued through midnight to about 11:00 a.m. the next day. Subjects were tested in groups of three or four and were not told whether they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 21 publications
2
51
1
Order By: Relevance
“…Confusingly, some studies reported significant psychomotor performance impairment (Takala, 1958;Kelly et al, 1970;Seppälä et al, 1976;Bonte and Volck, 1978;Myrsten et al, 1980;Laurell and Törnros, 1983;Yesavage and Von Leirer, 1986;Roehrs et al, 1991;Yesavage et al, 1994;Anderson and Dawson, 1999), whereas other studies did not (Carroll et al, 1964;Ideström and Cadenius, 1968;Dowd et al, 1973;Collins and Chiles, 1980;Collins, 1980;Morrow et al, 1990;Törnros and Laurell, 1991;Lemon et al, 1993;Chait and Perry, 1994;Streufert et al, 1995;Taylor et al, 1996;Finnigan et al, 1998). Taking into account that the majority of participants in these studies did report hangover symptoms, the inconclusive results are rather unexpected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confusingly, some studies reported significant psychomotor performance impairment (Takala, 1958;Kelly et al, 1970;Seppälä et al, 1976;Bonte and Volck, 1978;Myrsten et al, 1980;Laurell and Törnros, 1983;Yesavage and Von Leirer, 1986;Roehrs et al, 1991;Yesavage et al, 1994;Anderson and Dawson, 1999), whereas other studies did not (Carroll et al, 1964;Ideström and Cadenius, 1968;Dowd et al, 1973;Collins and Chiles, 1980;Collins, 1980;Morrow et al, 1990;Törnros and Laurell, 1991;Lemon et al, 1993;Chait and Perry, 1994;Streufert et al, 1995;Taylor et al, 1996;Finnigan et al, 1998). Taking into account that the majority of participants in these studies did report hangover symptoms, the inconclusive results are rather unexpected.…”
Section: Introductionmentioning
confidence: 99%
“…Results from these studies are difficult to interpret, since normally binge drinking takes place during the evening or night. Finally, in some studies participants received less than 6 h of sleeping time before next-morning tests started (Collins and Chiles, 1980;Collins, 1980). In these studies, the effects of sleep restriction probably interfere with the effects caused by binge drinking itself.…”
Section: Introductionmentioning
confidence: 99%
“…simulator provided a sensitive means by which to study the effects of drug stress on pilots. Flight simulators have been used by a number of investigators to study the effects of ethanol on pilot performance (8,9,10,11,12). Performance decrements have been found at moderate blood alcohol levels (.05 BAL and above).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have found dependent variables involved in a pilot's control of a flight simulator to be sensitive to the following toxic substances: secobarbitol (7); alcohol, (8,9,10,11,12); marijuana, (13); and anti-emetic drugs, (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation